2012
DOI: 10.1063/1.4736568
|View full text |Cite
|
Sign up to set email alerts
|

Methane and carbon dioxide adsorption on edge-functionalized graphene: A comparative DFT study

Abstract: With a view towards optimizing gas storage and separation in crystalline and disordered nanoporous carbon-based materials, we use ab initio density functional theory calculations to explore the effect of chemical functionalization on gas binding to exposed edges within model carbon nanostructures. We test the geometry, energetics, and charge distribution of in-plane and out-of-plane binding of CO(2) and CH(4) to model zigzag graphene nanoribbons edge-functionalized with COOH, OH, NH(2), H(2)PO(3), NO(2), and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 71 publications
5
61
0
3
Order By: Relevance
“…Wood et al 19 and references therein) both for gas storage or catalysis, since the particular location of adsorbents or reactants within the substrate is crucial to evaluate whether the adsorbent material has the desired properties. This is in principle a challenging theoretical problem, in which we have to solve the statistical mechanics of a fluid in the presence of a highly non-uniform (and topologically disordered) external field stemming from the adsorbent matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Wood et al 19 and references therein) both for gas storage or catalysis, since the particular location of adsorbents or reactants within the substrate is crucial to evaluate whether the adsorbent material has the desired properties. This is in principle a challenging theoretical problem, in which we have to solve the statistical mechanics of a fluid in the presence of a highly non-uniform (and topologically disordered) external field stemming from the adsorbent matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[151][152][153][154] Wood and Pathak used DFT to determine the geometry and energetics of CH 4 and CO 2 adsorbed on zigzag graphene nanoribbons (ZGNRs) with attached chemical functional groups. 151 The authors showed that polar groups (COOH, NH 2 , NO 2 , and H 2 PO 3 ) are promising candidates for enhancing CO 2 and CH 4 adsorption capacity by strengthening adsorption and activating exposed edges and terraces to introduce additional binding sites. This result has important implications for improving uptake in carbon structures that are known to have high quantities of edge carbons.…”
Section: Gas Adsorptionmentioning
confidence: 99%
“…The varying band gaps of these new materials and other carbon nanostructures include extensively a wide range of conductivity with all the potential applications in semiconductor (Mukherjee and Kaloni 2012;Kaloni et al 2014), conductor (Ataca et al 2008) to superconductor (Ugeda et al 2010). The easily tunable structural stability, band structure and other electronic/magnetic properties, and also photonic and vibrational properties of graphene have been achieved through a number of techniques like: via vacancies Ugeda et al 2010;Singh et al 2013;Kaloni et al 2012), atomic/molecular doping (Medeiros et al 2010;Johll et al 2009;Thapa et al 2011;Chan et al 2008;Karki and Adhikari 2014;Saha et al 2009;Wu and Yang 2012), functionalization (Wood et al 2012;Ulman et al 2014), irradiation (Esquinazi et al 2003) and external fields (Park and Louie 2010). The modified compounds carry potential applications over many dimensions like in electronics (Geim 2009;Novoselov et al 2005Novoselov et al , 2007, spintronics (Palacios et al 2008;Ding et al 2011), chemical sensors (Saha et al 2009), and energy storage (Pumera 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The modified compounds carry potential applications over many dimensions like in electronics (Geim 2009;Novoselov et al 2005Novoselov et al , 2007, spintronics (Palacios et al 2008;Ding et al 2011), chemical sensors (Saha et al 2009), and energy storage (Pumera 2011). Graphene with the adsorption of relevant metal atoms, clusters and other functional groups as impurities have been seriously considered and studied as substrates for gaseous adsorption (Wu and Yang 2012), including energy carrying gases methane and hydrogen (Wood et al 2012;Ulman et al 2014).…”
Section: Introductionmentioning
confidence: 99%